2004
DOI: 10.1080/09674845.2004.11732649
|View full text |Cite
|
Sign up to set email alerts
|

Folate and homocysteine levels in pregnancy

Abstract: This study aims to determine serum folate and plasma homocysteine levels in healthy pregnant women following a live birth and compare them with healthy non-pregnant women. Fifty healthy gravid multiparous women are included in the study and 25 normal non-pregnant female subjects act as controls (group I). The pregnant women are divided into two groups according to interpregnancy interval: group II (six months or less); group III (18-24 months). Venous blood samples are analysed for red blood cell folate and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 28 publications
0
19
3
Order By: Relevance
“…It needs folate as a substrate and vitamin B12 as a coenzyme. The absence or lack of any of these will lead to homocysteine accumulation (16). In several studies, the reverse correlation between levels of serum folate and homocysteine has been demonstrated (9, 10, 16, 20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It needs folate as a substrate and vitamin B12 as a coenzyme. The absence or lack of any of these will lead to homocysteine accumulation (16). In several studies, the reverse correlation between levels of serum folate and homocysteine has been demonstrated (9, 10, 16, 20).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown higher levels of homocysteine in preeclamptic women; they are detected in early pregnancy and remain elevated until delivery (15). Low maternal folate concentrations are associated with preeclampsia (9, 10, 16). The ability to screen women at risk for preeclampsia would increase the potential for strategies of prevention (8).…”
Section: Introductionmentioning
confidence: 99%
“…A survey in urban adult population in South India also observed an age-related decrease in folic acid levels [33]. The folic acid deficiencies are likely to worsen with subsequent pregnancies [41] especially where the birth interval is short [42]. Vitamin B12 levels were not found to be associated with age, parity or current pregnancy and breastfeeding status.…”
Section: Discussionmentioning
confidence: 99%
“…If this disease is influenced by maternal nutrient intake, we speculate that the period of fetal risk is most likely the last months of brain development before birth when folate intake levels are low, and not the embryonic and early fetal period when the gross structure of the central nervous system is developing as nutrient intake levels are at their highest at this stage. Folate catabolism peaks in the third trimester when there is a maximal increase in fetal mass (Megahed and Taher, 2004). In later pregnancy, folate inadequacy results in intrauterine growth retardation possibly as a result of impaired cell proliferation and folate dependant vitamin and amino-acid metabolism (Scholl and Johnson, 2000).…”
Section: Winter Birth and Schizophreniamentioning
confidence: 99%